POTENSI RAINWATER HARVESTING DALAM MENGURANGI RISIKO KEKERINGAN DI KABUPATEN KARAWANG - Dian Afifah Rahmawati; Eka Oktariyanto Nugroho; Muhammad Syahril Badri Kusuma; M. Cahyono; Imroatul C. Juliana; Taufik Ari Gunawan (Jurnal Riset Rekayasa Sipil, 2023)
Drought occurs quite often in Indonesia, closely related to water availability for community needs. One of the districts in West Java Province experiencing drought problems is Karawang district, where the RWH (Rainwater Harvesting) concept will be applied. This study aimed to analyze the risk of drought-related to applying the potential RWH in reducing drought risk. This study only focuses on meteorological drought, determined by SPI (Standardized Precipitation Index). Identification of potential areas for the application of RWH is carried out using the Weighted Method Overlay approach in the Geographic Information System (GIS), which was modified by adding a parameter of potential drought hazard. The potential reliability of RWH, as seen from Volumetric Reliability (VR) for supplying the average water requirement of MCK (Bath Washing Toilet) per year, indicates that most of the Karawang district area is potential for applying RWH. The results of adding the potential drought hazard parameters on applying the RWH concept show the decreasing area of very potential and potential category areas into 5,38%, the increase of drought resistance capacity is 17.5%, and the risk-reducing to 8.3%. Those results are due to the changes in the area of drought in the risk analysis. The assumptions of 60 rainy days on the average rainy day in a year and all households making RWH storage systems were used in the analysis. The results of this study can be used as a first step to see the potential of RWH in Karawang Regency both in terms of area and reliability.